Census of State and Federal Adult Correctional Facilities, 1990 ([Verlag nicht ermittelbar], 1993)
This census is the fourth enumeration of state adult correctional institutions and the first of federal institutions sponsored by the Bureau of Justice Statistics and conducted by the Bureau of the Census. Earlier censuses were completed in 1974 (ICPSR 7811), 1979 (ICPSR 7852), and 1984 (ICPSR 8444). Separate questionnaires were devised for confinement facilities and for community-based facilities. Variables describing the facilities include physical security, age, functions, capacity, confinement space, available medical facilities, programs, inmate/resident work assignments, staff employment, facilities under court order/consent decree for conditions of confinement, capital and operating expenditures, custody level of inmates/residents, one-day count and average daily population, race/ethnicity of inmates/residents, inmate/resident deaths, special inmate/resident counts, and assaults and incidents by inmates. An addendum on drug control activities in state and federal facilities was included for the first time in the 1990 census. Facilities were asked to provide information on the following: procedures used with inmates/residents, visitors, and staff to keep out illegal drugs and drug paraphernalia, inmate/resident drug-testing practices, including the criteria for testing inmates/residents, the number of inmates/residents tested in total and by specific drug, and the number that tested positive, staff drug testing, including groups and basis for testing, number tested, and procedures when tests were positive, and capacity and enrollment in various types of drug treatment and intervention programs.